2019
DOI: 10.1155/2019/1089578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in the Middle Belt of Ghana: A Community-Based Screening Study

Abstract: Objective Prevalence of hypertension is on the rise and can be attributed to aging populations and changing behavioral or lifestyle risk factors. The objectives of this study were to determine the prevalence, awareness, treatment, control, and risk factors of hypertension in the middle part of Ghana. Methods A total of 2,555 participants aged ≥18 years (mean age of 43 years; 60.5% female) were enrolled using a two-stage sampling method. The World Health Organization STEPwise approach to chronic disease risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
(34 reference statements)
2
40
2
2
Order By: Relevance
“…19 These are likely contributors to the increasing burden of NCDs such as obesity, hypertension and diabetes mellitus in Ghana. [20][21][22] The prevalence of these diseases is higher in older adults. These adults are also less likely to have the financial resources to spend on these diseases as they are often past their prime working lives at this time.…”
Section: Introductionmentioning
confidence: 99%
“…19 These are likely contributors to the increasing burden of NCDs such as obesity, hypertension and diabetes mellitus in Ghana. [20][21][22] The prevalence of these diseases is higher in older adults. These adults are also less likely to have the financial resources to spend on these diseases as they are often past their prime working lives at this time.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed a significant proportion of respondents with a high prevalence of CV risk factors. [31] and Ghana [32] respectively. The higher prevalence could result from the use of a high-risk population of civil servants compared with the use of the general population in the three studies.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of the population have valid health insurance cards that enable them to access basic healthcare under the National Health Insurance Scheme. In 2016, 2555 community members aged ≥ 18 years (mean age of 43 years, SD 17; 60.5% female) participated in a cross-sectional health survey, which documents the prevalence of hypertension as 28.1% (95% CI 26.3-29.8), with pre-hypertension prevalence of 42.5% [28]. Approximately 45.9% (95% CI 42.2-49.6) of hypertensive respondents were aware of their diagnosis; of those aware, 41.3 (95% CI 36.1-46.8) sought medical treatment and had their hypertension controlled, while 58.7% (95% CI 53.2-63.9) did not seek any medical treatment.…”
Section: Study Setting and Participant Characteristicsmentioning
confidence: 99%
“…Approximately 45.9% (95% CI 42.2-49.6) of hypertensive respondents were aware of their diagnosis; of those aware, 41.3 (95% CI 36.1-46.8) sought medical treatment and had their hypertension controlled, while 58.7% (95% CI 53.2-63.9) did not seek any medical treatment. Tobacco use in the area is about 3%, and the prevalence rate of obesity among the adult population (> 40 years) is 11% [28].…”
Section: Study Setting and Participant Characteristicsmentioning
confidence: 99%